Analysis of Network Security Countermeasures From the Perspective of Improved FS Algorithm and ICT Convergence - Zhang, Zhihong (Journal of Cyber Security and Mobility, 2023)
In this paper, the forward selection (FS) algorithm is introduced on the basis of information and communication technology, and the design of intrusion detection method for communication network is carried out. By studying the classification and detection pattern matching of communication network intrusion behavior, extracting the intrusion behavior features of communication network based on FS algorithm, and optimizing the intrusion detection and learning effect based on the limit learning machine, the intrusion behavior attributes of communication network are clarified, and a new detection method is proposed to solve the problems of low detection accuracy and low recall in the current intrusion behavior detection of complex communication network environments. Compared with the intrusion detection method based on GA-SVM algorithm, the accuracy of the detection results reaches 94.23%, and the recall rate exceeds 97%, which is obviously better than the 85% accuracy and 75% recall rate of the traditional detection method, which can ensure the security of the communication network environment. In addition, this paper proposes the APDR dynamic comprehensive information security assurance system model, which has considerable flexibility and can respond to current network security requirements.